Four Aspects of Architectural Tectonics Through Exploration of the Meaning of Tectonics with a Systematic Literature Review Method - Yashinta Irma Pratami Hematang; Ikaputra Ikaputra (Journal of Architectural Design and Urbanism, 2022)
Architectural tectonics which has a meaningful relationship with aesthetic and construction aspects in buildings is still sometimes understood separately from one another. In addition to the need for architectural practice and education, in this context, this article seeks to enrich the meaning of architectural tectonics by exploring and synthesizing meaning from leading online and architectural dictionaries as well as various libraries of journals, proceedings, reports, and architectural books. Tectonics in architectural research and design still needs to be explored where this concept can be useful in the design process because it does not separate structure and aesthetics in architecture. In this study, it is known that there have been various theories from architectural experts about the architectural tectonic theory from 1781 to 2022. This research is a literature review method with a systematic review method with synthesis results through narrative (qualitative) techniques from analogy processes and meaning synthesis. The results of this study, among others, produce the meaning of tectonic in synthesis 1, namely architectural tectonics in aspects of the appearance on the surface, aspects of tectonics processes, and aspects of internal factors. Meanwhile, in synthesis 2, other aspects were produced outside of the three aspects in synthesis 1.